Before and beyond divergence the politics of economic change in China and Europe - Rosenthal, Jean-Laurent; Wong, Roy Bin (Harvard University Press, 2011)
Rosenthal and Wong show that relative prices matter to how economies evolve; institutions can have a large effect on relative prices; and the spatial scale of polities can affect the choices of institutions in the long run. Their perspective on institutional change has implications for understanding transformations in China